Mortality associated with the use of digoxin in the treatment of atrial fibrillation: an integrative review (Research, Society and Development, 2021)
Atrial fibrillation (AF) is the most prevalent arrhythmia, triggering an irregular and fast heart rhythm. Although it is not always the drug of first choice, digoxin is still widely used, although there is a fine line between its therapeutic effects, adverse effects, and mortality. Therefore, the aim of this study is to seek clinical evidence on the correlation between the use of digoxin and mortality in patients with AF. Thus, a literature search was conducted using the descriptors "(Digoxin) AND (Atrial fibrillation) AND (drug therapy)" in the PubMed, Virtual Health Library (VHL), Scientific Electronic Library Online (Scielo) and Cochrane databases. The search was conducted during the month of February 2021. After applying the defined inclusion criteria, 15 studies were selected. After analysis, it was evident the increasing number of studies that relate mortality to digoxin therapy in patients with AF and in association with comorbidities, such as heart failure (HF). Therefore, although there is no consensus, mortality was higher in groups of patients with AF, with or without cardioverter defibrillator, who used digoxin; mortality was even higher in the elderly, in patients with kidney disease, in patients with AF without HF and in the absence of therapeutic monitoring. Given the evidence presented in this review, we can state that the use of digoxin in patients with AF should be avoided or undertaken with caution and close monitoring.